Physical metallurgy and advanced materials. - Smallman, R. E. (Butterworth Heinemann, 2007)
Physical Metallurgy and Advanced Materials is the latest edition of the classic book previously published as Modern Physical Metallurgy & Materials Engineering. Fully revised and expanded, this new edition develops on its predecessor by including detailed coverage of the latest topics in metallurgy and material science. Intended for senior undergraduates and graduate students it emphasises the science, production and applications of engineering materials. It is suitable for all post-introductory materials science courses.
Keywords: Physical metallurgy.; elektronické knihy; electronic books